PERCEPTION OF SPORTS OBJECTS POSITION INSIDE EDUCATIONAL-PROFESSIONAL STATUS OF GRAMMAR SCHOOL STUDENTS - Danijela Bonacin; Dobromir Bonacin (University of Banja Luka, Faculty of physical education and sport, 2010)
Numerous researches have shown that the high school pupils, whose adolescence is coming toan end, are in a very delicate choice situation. The peculiarity of their personal status enables theenvironment to exert influence on them and if possible to model their attitudes towards personalinterests, thus, in a way, guiding them. That is why, each research into this population which aimsto further their development and model a better quality future, is welcome in any form, and thatis why that population is the topic of this paper. Taking into consideration that in the contempo-rary world, there is a general tendency to increase the level of education and emphasize the im-portance of professionalism in all walks of life, and on the other hand, there is a tendency toamplify the construction of different facilities, the issue tackled in this paper is how to define therelation between the education-professional status and sports buildings in the grammar highschool students population in order to recognize the dynamic relations of those variables so as topossibly offer some conclusions and consequently adequate suggestions and upbringing-educa-tion guidelines. To resolve the issue, we used a sample of 400 pupils from the first to the fourthgrade of the grammar school, described with 8 variables describing the education and profes-sional status and 3 variables describing the sports facilities. The data were collected via a survey(author: Danijela Bonancin). After the normalization, a classic canonical correlational analysis wasperformed so as to establish linear combinations between the two sets of variables. The resultsobtained indicate the existence of two out of the possible three canonical factors, that is, twoways of linking the sets whereby one of them is somewhat more prominent. The results show anobvious existence of conservatism, social egoism, perhaps even selfishness among the existingpopulation. Since some other researches showed that girls of the same age and from the samearea were inclined to learning and changing, and being aware of that, they have a more positiveopinion, the results of this paper can be explained to some extent by the mode of thinking pre-vailing in the surveyed community where maybe the sons - the heirs are placed on the pedestaland perhaps glorified a bit too much. It is likely that male children are led by the system towardsthe goal without inciting them to fight for it on their own. That is why they do not want change,they do not want to study, and as a consequence of that, they want it all for themselves.